Supersymmetric models and their phenomenology - Ross, G (1995)
The prospects for unification of the Standard Model are considered and the need for supersymmetry discussed. The prediction of the gauge couplings, the electroweak breaking scale, the fermion masses and the dark matter abundance are all consistent with Simple unification if there is a stage of supersymmetric unification below the TeV scale. The prospects for discovery of the new SUSY states is considered, both in the minimal supersymmetric standard model and in non-minimal extensions.